PROTECTING SCHOOLS WITHIN CONFLICT ZONES IN GAZA STRIP UNDER INTERNATIONAL HUMANITARIAN LAW - Alburai, Dima (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The paper has discussed the violation against education facilities in Gaza Strip from the International Humanitarian Law (IHL) perspective, explaining the challenges and the impact of armed conflict on education rights. The paper will identify those violations and will propose methodologies to improve the adoption of the IHL against them. Moreover, it will discuss the policies to decrease the impact of those violations and propose techniques to respond to the threats against children’s rights within the war duration. It will be analyzed the applied IHL in the protection of the education system in Gaza Strip from the attack which happened in 2021 by exploring the efficiency of the IHL impartially. In this research, a qualitative approach has been adopted as a primary source in exploring how educational institutions should be protected within IHL (which should be respected) during attacks. As per the descriptive study, the research will investigate the importance of protecting children’s educational institutions in armed conflict situations. The assessment of child protection was considered in the escalation of Israeli attacks on the Gaza Strip in May 2021. The main source of data has been collected using different media such as Telephone-based semi-structured interviews, E-mail correspondence, documentary review, and agencies working in child protection in Gaza Strip; in addition, other secondary sources have been considered, such as desk review, reliable journalism, and published academic research. Continuous military operations throughout Gaza Strip compose dramatic challenges to getting highly qualified education in a safe environment for children. The air strikes and rocket attacks prevented 637,195 students from being in school in a safe environment. Other reports addressed that Israeli airstrikes destroyed over 184 schools in 2021 and caused partial or severe damage to others. As addressed in other reports, the students and the academic staff have suffered from different cases of depression and expressed their fears of asymmetric warfare in addition to being under blockage (OCHA, May 2021). Regarding the laws governing educational facilities and institutions’ protection, IHL still has some space for improvement that can be addressed and applied in the future to enhance them. It is known that numerous kid fatalities and schools suffered partial or total destruction as a result of military activities. On the same, it is documented that the levels of violence against educational organizations and schools hit unheard-of levels in the last ten years.